2019
DOI: 10.1037/ser0000213
|View full text |Cite
|
Sign up to set email alerts
|

Changes in psychiatric symptoms and psychological processes among veterans participating in a therapeutic adventure program.

Abstract: When veterans need effective mental health treatment, many are reluctant to engage in traditional treatment modalities because of stigma. Therapeutic adventure shows promise as a way to engage veterans and enact positive changes in functioning, but little is known about how therapeutic adventure impacts mental health symptoms among veterans. This study examined changes in mental health symptoms and related psychological processes over the course of a 6-day Outward Bound for Veterans (OB4V) program and at a 1-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…It is important to note that these improvements are in the context of ongoing psychological treatment, with over 70% of participants receiving treatment at the time of the program. However, our results are consistent with outcomes from other peer-to-peer interventions (Nelson et al, 2014;Possemato et al, 2019;Romaniuk et al, 2019) and adventure-based therapeutic programs such as Outward Bound for Veterans (OB4V), a similar program to Trojan's Trek in the US and Canada (Bettmann et al, 2019;Ewert, 2014;Harper et al, 2014;Scheinfeld et al, 2017;Scheinfeld & Spangler, 2013). In a recent study by Bettmann and colleagues (2019), 77 ex-service personnel taking part in the 6-day OB4V program reported significant improvements including increased life purpose satisfaction and self-confidence post-program and decreased mental health symptomology at follow-up.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…It is important to note that these improvements are in the context of ongoing psychological treatment, with over 70% of participants receiving treatment at the time of the program. However, our results are consistent with outcomes from other peer-to-peer interventions (Nelson et al, 2014;Possemato et al, 2019;Romaniuk et al, 2019) and adventure-based therapeutic programs such as Outward Bound for Veterans (OB4V), a similar program to Trojan's Trek in the US and Canada (Bettmann et al, 2019;Ewert, 2014;Harper et al, 2014;Scheinfeld et al, 2017;Scheinfeld & Spangler, 2013). In a recent study by Bettmann and colleagues (2019), 77 ex-service personnel taking part in the 6-day OB4V program reported significant improvements including increased life purpose satisfaction and self-confidence post-program and decreased mental health symptomology at follow-up.…”
Section: Discussionsupporting
confidence: 84%
“…In a systematic review, self-efficacy was significantly negatively correlated with posttraumatic stress following multiple types of trauma (Simmen-Janevska et al, 2012). Previous studies have also suggested both adventurebased therapy and peer-to-peer interventions may help to maintain positive outcomes through improved attitudes towards help-seeking (Bettmann et al, 2019;Hamblen et al, 2019;Jain et al, 2013). However, help-seeking was already high in this cohort, with over 70% of participants reporting current psychological treatment.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In recent years, a number of support programs have emerged to help address issues surrounding OSI and transition from military to civilian life, such as OSI clinics, available through CAF or nongovernment organizations (NGOs), like Outward Bound Canada (Harper, Norris, & D'Astous, 2014) and Warrior Adventures Canada (Warrior Adventures Canada, 2018). Similar programs in the United States include Outward Bound for Vets (OB4V) (Bettmann, Scheinfeld, Prince, Garland, & Ovrom, 2018;Scheinfeld et al, 2017) and Warrior Adventure Quest (WAQ) (Hayden, 2010;McIlvaine, 2008). Outdoor-based programs have been gaining popularity as an alternative to traditional programming (Scheinfeld et al, 2017), citing the mental health benefits to veterans including improvements in ''coping skills, stress management, problem solving, communication, self-esteem building and community reintegration'' (Greer & Vin-Raviv, 2019).…”
mentioning
confidence: 99%